Immunosuppressive therapy modulates T lymphocyte gene expression in patients with systemic lupus erythematosus - Pereira, Elayne (Blackwell Science Inc, 2004)
To evaluate the T-cell large-scale differential gene expression in systemic lupus erythematosus (SLE) patients presenting with glomerulonephritis we studied SLE patients before and after immunosuppressive treatment. Large-scale gene expression of peripheral blood mononuclear T cells was evaluated using cDNA microarray nylon membranes containing 5184 cDNAs. Data were analysed using the SAM and Cluster and Treeview software. When untreated patients were compared to healthy individuals, 38 genes, most of them located on chromosomes 1, 3, 6, 17 and 19, were repressed, and when untreated patients were compared to treated ones, 154 genes, located on chromosomes 1, 6, 7, 12 and 17, were induced. In terms of biological function of coded proteins, the differentially expressed genes were associated with apoptosis, cell cycle, chromosomal scaffold, cytokine/chemokine, DNA repair/replication, Golgi/mitochondrial proteins, mRNA processing, signalling molecules and tumour suppressors. Two autoantigen genes related to RNA splicing (small nuclear riboprotein 70 000 MW-U1 SNR, and splicing factor 3a, 60 000 MW), and the tetranectin-plasminogen-binding protein were repressed. The Fc fragment of immunoglobulin G low affinity IIb, apoptotic protease activating factor-1, two subunits of cytochrome c, caspase 8, complement C5a, HLA-DRA, HLA-DQB1, transforming growth factor-β receptor II, small nuclear ribonucleoprotein polypeptide N (Sm protein N) genes, heterogeneous nuclear riboprotein-C, and argininosuccinate lyase genes, among others, were induced. A total of 10 genes were repressed in untreated patients and induced in treated ones, among them tumour necrosis factor (ligand) superfamily member 9, tumour protein p53, mannosidase alpha class IA, and CD22. Although some of these differentially expressed genes are typically expressed in B cells, CD22 and CD32 have also been reported in T cells and may provide regulatory signals to B cells. Assessment of differential gene expression may provide hybridization signatures that may identify susceptibility, diagnostic and prognostic markers of SLE.